Community-based management of acute malnutrition (CMAM) in India: a position paper - Mathur, Meeta; Halim, Abdul; Gupta, Mousumi; Panda, Bijayalaxmi; Syed, Arish (International Journal of Research in Medical Sciences, 2018)
Considering the burden of Severely Acute Malnutrition (SAM) in India and the availability of SAM treatment at facility level, it is operationally not feasible to treat all SAM children. The community- based approach involves timely detection of severe acute malnutrition in the community and the provision of treatment for those without medical complications with ready-to-use therapeutic foods or other nutrient-dense foods at home. Community based Management of Acute Malnutrition (CMAM) is an integrated approach which on one hand focuses on treatment and on the other prevention. CMAM has a key component of community mobilization which is crucial for prevention. The present paper emphasizes the position of CMAM in India in terms of preventive vs curative, integrative approach, multi sectoral engagement, mental health perspective as per the facts available through secondary sources in India and also experiences of CMAM-I phase implemented in Rajasthan. A CMAM programme can be an ideal and well established programme considering the inclusion of different aspects such as alternative feasible solution, convergent action, multi-stakeholders roles and accountabilities.